2020
DOI: 10.1093/mnras/staa2426
|View full text |Cite
|
Sign up to set email alerts
|

The Blanco DECam bulge survey. I. The survey description and early results

Abstract: The Blanco Dark Energy Camera (DECam) Bulge survey is a Vera Rubin Observatory (LSST) pathfinder imaging survey, spanning ∼200 sq. deg. of the Southern Galactic bulge, −2○ <b<−13○ and −11○ <l<+11○. We have employed the CTIO-4m telescope and the Dark Energy Camera (DECam) to image a contiguous ∼200 sq. deg. region of the relatively less reddened Southern Galactic bulge, in SDSS u + Pan-STARRSgrizy. Optical photometry with its large colour baseline will be used to investigate the age … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 70 publications
2
16
0
Order By: Relevance
“…Taking the 𝐼-band component luminosities from Flynn et al (2006), this implies a bulge/bar 𝐵-𝐼 of 2.41. This compares well with Galactic bulge observations through the relatively dust-free Baade's window (Rich et al 2020;Lim et al 2021). The inferred disc colour is 1.62, bluer than the total integrated colour as expected, and 0.14 redder than the dust-corrected Flynn et al (2006) value for the local disc.…”
Section: Armssupporting
confidence: 83%
“…Taking the 𝐼-band component luminosities from Flynn et al (2006), this implies a bulge/bar 𝐵-𝐼 of 2.41. This compares well with Galactic bulge observations through the relatively dust-free Baade's window (Rich et al 2020;Lim et al 2021). The inferred disc colour is 1.62, bluer than the total integrated colour as expected, and 0.14 redder than the dust-corrected Flynn et al (2006) value for the local disc.…”
Section: Armssupporting
confidence: 83%
“…Additionally, Barbuy et al (2018) noted that the CMD simulation in Haywood et al (2016) that included a prominent young population produced too many bright main-sequence turn-off stars and thus may be incompatible with observations. A similar discrepancy is seen in the possible discovery of young (∼1 Gyr) blue loop stars in Baade's Window by Saha et al (2019), which are shown by Rich et al (2020) to instead be nearby stars in the disk.…”
supporting
confidence: 58%
“…For this work, we have isolated a sample of ∼ 2.6 million red clump stars spanning |l| < 10 • and −10 • < b < −3.5 • from the BDBS catalog (Johnson et al 2020;Rich et al 2020). We applied Gaia EDR3 proper motions and parallaxes to remove likely foreground contamination, and also determined distance estimates from a metallicity-dependent calibration of dereddened i-band photometry based on 10 Gyr stellar isochrones.…”
Section: Discussionmentioning
confidence: 99%
“…As an independent check, we also attempt to perform age derivations from photometric sub-samples of the same population using the Blanco DECam Bulge Survey (BDBS; Rich et al 2020;Johnson et al 2020) and Gaia EDR3 (Gaia Collaboration et al 2021). While we can produce an age-metallicity distribution visually consistent with the absence of an age gradient-and almost totally bereft of young stars-in both cases, our attempts to compute observational age uncertainties reveal that the photometric parameters are simply too imprecise to provide meaningful estimates of either the ages or their uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…acknowledges an ESO Fellowship. AGE FITS USING PHOTOMETRIC SYSTEMS As an independent check on our age determinations fromBensby et al (2017)'s own measurements, we attempt to derive ages from colors and magnitudes for those B17 sources which also have photometry from the Blanco DECam Bulge Survey (BDBS;Rich et al 2020;Johnson et al 2020) and/or Gaia EDR3(Gaia Collaboration et al 2021). AmongBensby et al (…”
mentioning
confidence: 99%